1997
DOI: 10.1210/jcem.82.8.4162
|View full text |Cite
|
Sign up to set email alerts
|

Troglitazone Ameliorates Insulin Resistance in Patients with Werner’s Syndrome

Abstract: Insulin resistance in Werner's syndrome (WS) is probably due to defective signaling distal to the insulin receptor. To analyze the metabolic effects of troglitazone (TRO) in these patients, we performed frequently sampled iv glucose tolerance tests. Glucose kinetics were analyzed by the minimal model. Five patients with WS (mean age, 41.2 yr; body mass index, 17.0 kg/m 2 ) were treated with TRO (400 mg/day) for 4 weeks. Each subject underwent a 75-g OGTT and frequently sampled iv glucose tolerance tests. Treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…However, we have found a lack of significant correlation between the acute insulin response and SG in the present as well as previous studies. 17,18 Based on these findings, we postulate that Japanese subjects probably suffer from impairment of ␤-cell function and glucose-dependent glucose uptake.…”
Section: Discussionmentioning
confidence: 95%
“…However, we have found a lack of significant correlation between the acute insulin response and SG in the present as well as previous studies. 17,18 Based on these findings, we postulate that Japanese subjects probably suffer from impairment of ␤-cell function and glucose-dependent glucose uptake.…”
Section: Discussionmentioning
confidence: 95%
“…One study revealed insulin‐resistant diabetes mellitus and visceral fat obesity in Werner syndrome patients 14 . The insulin resistance in Werner syndrome is attributed to the intracellular insulin signaling defect 15 . In our case, abdominal computed tomography did not reveal any visceral fat obesity.…”
Section: Discussionmentioning
confidence: 41%
“…It is suggested that MCC-555 may provide a causal therapy of insulin resistance by targeted action on the defective site in the insulin signaling cascade. Further, the drugs may also be suitable for treatment of nondiabetic insulin-resistant states such as obesity (11), the polycystic ovarian syndrome (12), and Werner's syndrome (13). 1 and 2).…”
mentioning
confidence: 99%